2020
DOI: 10.21203/rs.2.19464/v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Determinants of Isoniazid Preventive Therapy Completion among People Living with HIV Attended Care and Treatment  Clinics from 2013 to 2017 in Dar es Salaam Region,Tanzania. A cross-sectional analytical study

Abstract: Background: Tuberculosis (TB) disease is a common opportunistic infection among people living with HIV (PLHIV). WHO recommends at least six months of isoniazid Preventive Therapy (IPT) to reduce the risk of active TB. It is important to monitor completion of IPT, as a suboptimal dose may not protect PLHIV from TB infection. This study determined IPT completion and its determinants among PLHIV aged 15 years or more in Dar es Salaam region, Tanzania. Methods: A Cross-sectional analytical study was conducted usin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In this case, the transfer-in facility may not offer care continuity (in this case INH) due to a lack of relevant documentation from the transfer-out facility (64). This finding is similar to a study done in Dar es salaam where people living with HIV who were transferred to other clinics within Dar es Salaam region after IPT initiation had significantly lower IPT completion levels compared to those that attended the same clinic (57). These findings are also similar to studies conducted in Zimbabwe and Ethiopia (26,65).…”
Section: Reasons For Ipt Non-completionsupporting
confidence: 74%
See 1 more Smart Citation
“…In this case, the transfer-in facility may not offer care continuity (in this case INH) due to a lack of relevant documentation from the transfer-out facility (64). This finding is similar to a study done in Dar es salaam where people living with HIV who were transferred to other clinics within Dar es Salaam region after IPT initiation had significantly lower IPT completion levels compared to those that attended the same clinic (57). These findings are also similar to studies conducted in Zimbabwe and Ethiopia (26,65).…”
Section: Reasons For Ipt Non-completionsupporting
confidence: 74%
“…Distance to the health facility was cited as one of the barriers to IPT completion as patients could not afford transport every month to the health facility to pick up their IPT doses. This echoes findings from studies conducted in Tanzania, Zimbabwe, and Ethiopia which found that patients were discouraged by the need to attend clinic every month combined with the long treatment duration of IPT (26,56,57). A significant proportion of patients do not get ART from their nearest facility (58,59) due to various reasons that include the fear of stigma, and the perception that care at local facilities being of lower quality compared to distant ones (59,60).…”
Section: Reasons For Ipt Non-completionmentioning
confidence: 60%